A Study of Pak-Turkey Convergence on International Issues (Al-Qamar, 2021)
Turkey, a grand empire remained centre of importance in history. Muslims conquered the area in her glory and converted it into a land of peace and prosperity. It was a centre of Islamic emporium for a long period. The lords of states gave up their true duty of being true with their compulsory obligations, left it skeleton of past power. First and second world wars proved a severe shell for it. As a result, with the passage of time, as the Blocks appeared on the face of modern politics, Balkan states joined the social block. In 1991, at the dismemberment the area got an awareness to get independence. Today Turkey developed itself into a moderate and developed Muslim state. Pak-Turk relations base on sincere and solid grounds from the very first day and provide close relations to both the nations. Today as a progressed Muslim state Turkey and Pakistan have very co-operative relations. It is the largest investor after China in Pakistan. This research paper is going to discuss Pak-Turk relations in this new era.
Keywords: Pakistan; Turkey; Convergence; International Issues